Detection of cardiac neuroendocrine tumour metastases by somatostatin receptor PET/CT: a systematic review and meta-analysis - Campanale, Daniela; Imperiale, Alessio; Albano, Domenico; Rizzo, Alessio; Piccardo, Arnoldo; Treglia, Giorgio (Frontiers in Medicine, 2024)
Background Cardiac neuroendocrine tumour metastases (CNTM) are rare, but advancements in molecular imaging including somatostatin receptor PET/CT (SSTR-PET/CT) could lead to a more frequent identification. The aim of this article is to perform a systematic review and meta-analysis on the detection of CNTM by SSTR-PET/CT. Methods A comprehensive literature search of studies on CNTM detected by SSTR-PET/CT was carried out. Three different bibliographic databases were screened (Cochrane library, PubMed/MEDLINE, EMBASE) until 20 August 2024. Two review authors independently selected the eligible original articles and performed the quality assessment and the data extraction. Main findings of eligible studies were summarized and a proportion meta-analysis on the prevalence of patients with CNTM among those with neuroendocrine neoplasm (NEN) performing SSTR-PET/CT was carried out using a random-effects model. Results Ten articles reporting data on 163 patients with CNTM were included in the systematic review. SSTR was able to detect CNTM earlier compared to other radiological imaging techniques. Most patients with CNTM had other metastatic sites and CNTM were often asymptomatic. The meta-analysis of seven articles demonstrated a pooled prevalence of 1.5% (95% confidence interval: 1.0–1.9%) of patients with CNTM (n = 119) among those performing SSTR-PET/CT for NEN (n = 9,300). Moderate statistical heterogeneity was found (I2 test: 62%). Conclusion Evidence-based data demonstrate that SSTR-PET/CT enables early and better detection of CNTM compared to other radiological imaging methods. CNTM are encountered with a pooled prevalence of 1.5% of NEN patients performing SSTR-PET/CT. Prospective and multicentric studies are warranted to better clarify the impact of CNTM detection by SSTR-PET/CT on overall survival and clinical decision-making in NEN patients.